“Dame Disease?”: A Note on the Gender of Philoctetes’ Wound - Bers, Victor (Hyperboreus, 2015)
Although Sophocles’ Philoctetes many times over refers to Philoctetes’ afﬂiction with a feminine noun, ἡ νόσος, Seth Schein’s recent commentary on the play is mistaken to refer to it as “female”.